Some unfinished chaos : the lives of F. Scott Fitzgerald - Krystal, Arthur (University of Virginia Press, 2023)
"A biography of F. Scott Fitzgerald, organized around three periods of Fitzgerald's life, offering considerations of Fitzgerald's life and art as well as of the larger context of life in America during those periods. Some Unfinished Chaos teases out Fitzgerald's many contradictions and charts our evolving relationship with this iconic author"--